Macro financial linkages in a SVAR model with application to Denmark - Jakob Roager Jensen; Jesper Pedersen (Danmarks Nationalbank, 2019)
We analyse macro financial linkages in the Danish economy by estimating a structural VAR model using Bayesian techniques and construct a new financial condition index for the Danish economy. We measure financial conditions as the aggregate impact of financial variables on real activity from the historical shock decomposition of GDP. We find that financial conditions have been an important driver of GDP in the Danish economy in recent years. Financial conditions stimulated GDP before the financial crisis and deepened the subsequent recession. Financial conditions have also contributed to the current expansion in the Danish economy. We compare the model properties with the properties of Danmarks Nationalbank's two other macroeconometric models and find striking similarities between the estimated VAR model and other models. The financial conditions index resembles the overall narrative of the Danish economy.
Keywords: C32; C54; E32; E44; E47; G17; 330; Economic activity; Financial markets; Models